MILESS CHARACTER IN LOOKING FOR ALASKA: A PSYCHOLOGYCAL PERSPECTIVE - Yani Heryani (Indonesian EFL Journal, 2016)
The aim of this research was to analyze the character of Miles Halter and the influences of the other characters towards Miless character in Looking for Alaska novel. The primary data source was transcribed from Looking for Alaska Novel directed by John Green (2005). Here, the researcher applied a descriptive qualitative research design based on theories of Roberts and Freud. To know how Miless character presented in the novel, the researcher used several ways such as from what Miles does and says and from what the other characters says about Miles. As result, the reseracher found that Miless characters were nice, independent, diligent, hard worker, naughty, curious, smart, and unique. Besides, the reseracher also found the influences from the other characters such as habitual in reading, smoking, drinking, and pranking.